A vertical diffusion method for the microbiological assay of isoniazid - Lloyd, Janet (1964)
A method is described for the assay of isoniazid in serum and other fluids by diffusion along slopes of Löwenstein-Jensen medium inoculated with tubercle bacilli. The method is convenient, rapid and robust, but is less accurate than diffusion systems for the assay of some other substances.